2022
DOI: 10.1111/puar.13452
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Motivation in Public Service: AThree‐PhaseLongitudinal Examination of Public Service Motivation, Work Values, and Academic Studies Among Israeli Students

Abstract: What are the impact of work values and academic training on public service motivation (PSM) over time? We present findings from a three‐phase longitudinal study on the evolvement of PSM of Israeli students who gradually enter the job market. A cohort of 2,799 students were surveyed in late 2012 and a surviving final cohort of 558 respondents took part in the third stage of data collection during early 2015. We analyzed this group's postgraduate career development when they joined various public and nonpublic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…The significance of this paper is to expand the scope of research on PSM theory and the applicability of the measurement dimensions. Many countries have explored the localization and group-specific applicability of PSM [ 44 , 45 , 46 , 48 ], and the specificity of research objects is the direction of future research on PSM. As an important force for social development, college students have their characteristics and are a large number of people who cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this paper is to expand the scope of research on PSM theory and the applicability of the measurement dimensions. Many countries have explored the localization and group-specific applicability of PSM [ 44 , 45 , 46 , 48 ], and the specificity of research objects is the direction of future research on PSM. As an important force for social development, college students have their characteristics and are a large number of people who cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Lundy et al (2018) [ 22 ] found that interprofessional educational experiences strengthen college students’ public service motivations, particularly in terms of public interest commitment and compassion. Miller et al (2022) [ 45 ] longitudinally studied the evolution of PSM in a cohort of Israeli students who gradually entered the job market and found that individuals with strong collectivism and an academic background in the core public service had higher PSM over time. Ngaruiya et al (2014) [ 46 ] found that ROTC (Reserve Officer Training Corps) participants had higher PSM based on the Kim Revised Scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, with few exceptions (e.g. Miller-Mor-Attias & Vigoda-Gadot, 2021; Andrews, 2021) PSM has been studied in a static fashion; motivations are captured in a snapshot or a particular moment. Insufficient attention is paid to changes in motivations over the course of individuals’ lives, and the interplay with the life-course dynamics of identities, roles, inequalities, and experiences.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This observation is particularly disconcerting since many fundamental public administration research questions relate to individual‐ or organization‐level temporal dynamics, or involve causality as an issue of temporal ordering. One can think, for example, about the impact of public sector reforms on organizational outputs and performance (Christensen & Lægreid, 2007; Levine, 1978, 1979; Wynen et al, 2019), the development of public service motivation or organizational citizenship behavior (Chen et al, 2023; Kim, 2021; Miller‐Mor‐Attias & Vigoda‐Gadot, 2022), the socialization of public sector employees (Moyson et al, 2018; Murdoch et al, 2019), the life cycle of public organizations (MacCarthaigh et al, 2012), or the short‐ and long‐term impact of representative bureaucracies on public policies (Ding et al, 2021; Gershenson et al, 2022). The persistent failure in much public administration research to take time and temporal dynamics seriously thus constitutes a major hindrance to the development of the profession.…”
Section: Introductionmentioning
confidence: 99%